KAJIAN EFEKTIFITAS GULLY PLUG DALAM PENGENDALIAN RUN OFF DI KAWASAN HULU DAS PULISAN - Kelvin Haryono Auwyanto; Tiny Mananoma; Jeffry S. F. Sumarauw (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The flood problem in Pulisan village that occurred in 2019 is one of the problems that needs to be addressed immediately because it causes losses to residents living around the river, and disrupts vehicle traffic. One of the causes of flooding in the Pulisan river is the magnitude of the run off and the large flow rate so that potential flooding events can occur. Therefore, run-off control is needed in the upstream area of the Pulisan river. Pulisan watershed has a total watershed area of 3.25 km2 and has 9 tributary channels. The location reviewed is in the Pulisan river channel with selected sections is the channel of 5 Pulisan rivers which has a watershed area of 0.2512 Km2. The Araren-Pigrandma MRG rain post and the Maen Climatology rain post are sources of maximum daily rainfall data used with a time span of 2002 to 2021. HEC-HMS software is used to obtain the parameters needed to obtain a peak discharge of 2.2 m3 / second and a planned flood discharge. HEC-RAS software to analyze water level and flow rate when using gully plug. The simulation results show that from several types of gully plugs, a significant reduction in flow speed is in type 60 gully plugs, namely the flow speed to 0.6 – 1 m / second, the flow speed does not cause deposits in the channel.